Industrial training report: MASwings / Nurul Izzati Janis - Janis, Nurul Izzati (Universiti Teknologi MARA, Sabah, 2020)
MASwings Sdn Bhd is a subordinate company of Malaysia Airlines, established on 1st October 2007. A regional airline based at Kota Kinabalu International Airport, Sabah (KKIA). Operating the Rural Air Services (RAS) in East Malaysia states of Sabah and Sarawak or known as Borneo. The headquarters location of this company is at MAS/MASwings Administration Building, Kota Kinabalu Airport, Sabah (KKIA).